Integrating Potential and Local Wisdom: Exploring the Ethnopedagogical Value of the Toraja Tribe in Biology Education - Sura, Sunarto Arif; Sriyati, Siti; Purwianingsih, Widi; Lembang, Angela Meirici (Yayasan Keluarga Guru Mandiri, 2026)
The Merdeka Curriculum is designed to provide flexibility and autonomy for schools in Indonesia to create learning experiences that align with local contexts and the individual needs of students. Education plays a vital role in integrating local potential and wisdom to achieve relevance at both the local and individual levels. Indonesia's rich cultural heritage offers numerous opportunities for integration into learning; however, many of these potentials remain underexplored and underutilized in scientific educational contexts. This study aims to identify and examine the potential and local wisdom of the Toraja people relevant to biological concepts and to develop an ethnopedagogical framework as a foundation for contextualized learning materials for senior high school students in Phases E and F. Employing a systematic literature review guided by the PRISMA model, the research screens, selects, and analyzes sources addressing the scientific relevance of the Toraja community's local potential and wisdom on topics such as biodiversity, genetics, anatomy, and more. Findings reveal that the local potential and indigenous knowledge embedded in Toraja wisdom can be adapted into scientific concepts that support the achievement of biology learning outcomes at the senior high school level in Phases E and F. This study contributes to the advancement of ethnopedagogy as an innovative educational approach that aligns teaching practices with local cultural values. Moreover, it provides a framework that can guide the development of learning content, modules, student worksheets, projects, quizzes, and assessment tools to foster meaningful and contextualized learning experiences.